Pengaruh Permainan Target Terhadap Kemampuan Shooting Pada Atlet Sepak Bola U-11 Di Safin Pati Sport School (SPSS) Tahun 2023 - Bagas Santya; Cahyo Yuwono; Harry Pramono; Martin Sudarmono (Universitas Negeri Semarang, 2024)
Target games could possibly be applied as a training program aimed at improving shooting accuracy which will be applied to U11s at the Safin Pati Sport School (SPSS). The aim of this research is to determine the effect of the target game on the shooting ability in the soccer game of Safin Pati Soccer Academy athletes. The type of data used in this research is quantitative data. The independent variable in this research is target play (X) while the dependent variable is shooting ability (Y). This research method is an experimental method using a one-group pretest posttest research design. The results of the research show that the shooting accuracy of Safin Pati Soccer Academy U-11 with a Sig (2 – tailed) value of 0.000 < 0.05. Ho: rejected and Ha:accepted so it can be concluded that there is a difference between the results of the pre-test and post-test shooting accuracy at Safin Pati Soccer Academy U-11, this could mean that there is an influence on shooting skills using the inside of the foot using a target on Safin Pati Soccer Academy. So, it can be concluded that